Moses: The Face of Fear - Koosed, Jennifer L. (Biblical interpretation, 2014)
Moses is the only prophet in the tradition to see God “face-to-face,” and this intimate contact transforms his very body – when he comes down from the mountain, his face is altered, and he must veil (Exod. 34:29–35). Both the altered face and the veiled face have strange interpretive histories. What may have begun in Hebrew as rays of light streaming from Moses’ visage become in Greek and Latin horns sticking out of his head; thus a history of interpretation begins which first avers the horns as symbols of power and divinity but later shifts to associate the horns with animals and demons. The veil may have also begun as a powerful symbol of prophecy, but its meaning also shifts, and it later becomes associated with passivity and femininity. These multivalent images reveal deeper realities and resonances. Moses is something other than, something beyond, the human and its gendered bifurcation. He is at the nexus where the human, the animal, and the divine meet and converge. And between the glowing face/horns and the veil lies fear, the fear of the Israelites when they behold their leader, and the fear of the Bible’s readers when they are faced with Moses’ ambiguities. Using affect theory, especially Sara Ahmed’s critical work on emotion, this paper will explore the meanings of Moses’ face, covered and uncovered, as it moves through time and community.